CircRNA hsa_circ_0004781 promoted cell proliferation by acting as a sponge for miR-9-5p and miR-338-3p and upregulating KLF5 and ADAM17 expression in pancreatic ductal adenocarcinoma - Kun-Lin Lee; Jun-Jen Liu; Wei-Jan Huang; Ching-Sheng Hung; Yu-Chih Liang (Cancer Cell International)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive types of solid tumor, and novel strategies must be developed for treating it. Previous studies predominantly utilized circular RNA (circRNA) expression plasmids incorporating Alu elements to facilitate the indirect expression of circRNA. Methods Public databases and bioinformatics tools were used to identify hsa_circ_0004781 that is highly expressed in PDAC and its potential microRNA (miRNA) targets and corresponding mRNA targets. Real hsa_circ_0004781, which is identical to the native form of hsa_circ_0004781 without any exogenous sequences, was prepared through in vitro transcription by using a ribozyme and ion-pair reversed-phase high-performance liquid chromatography (IP-RP HPLC). The biological functions of hsa_circ_0004781 were evaluated using loss-of-function and gain-of-function approaches with circRNA expression plasmids and real hsa_circ_0004781. Results Knockdown of hsa_circ_0004781 inhibited the proliferation and migration of PDAC cells, whereas its overexpression produced opposite effects. Hsa_circ_0004781 was identified as a sponge for miR-9-5p and miR-338-3p, and its expression was negatively correlated with that of these miRNAs. Among the targets of miR-9-5p and miR-338-3p, Kruppel-like factor 5 (KLF5) and a disintegrin and metalloproteinase domain 17 (ADAM17) were negatively correlated with survival in patients with PDAC and were inversely regulated by these miRNAs. Furthermore, real hsa_circ_0004781 exhibited the same effects as those of the circRNA expression plasmids. Conclusions This study is the first to use real circRNAs to validate results obtained using circRNA expression plasmids. The results suggest that hsa_circ_0004781 functions as an oncogene, promoting the proliferation of PDAC cells through the miR-9-5p/KLF5 and miR-338-3p/ADAM17 axes. Therefore, hsa_circ_0004781 might be a therapeutic target for PDAC.